Short-term effectiveness of ceftriaxone single dose in the initial treatment of acute uncomplicated pyelonephritis in women. A randomised controlled trial. Issue 1 (1st January 2002) - Sanchez, M; Collvinent, B; Miró, Ò; Horcajada, J P; Moreno, A; Marco, F; Mensa, J; Millá, J
Abstract : Objective: To compare the short-term effectiveness of ceftriaxone single dose followed by cefixime with a standard treatment of acute uncomplicated pyelonephritis in women. Methods: An open, prospective, and randomised trial of women with acute uncomplicated pyelonephritis was performed. Group A were given a daily intravenous dose of 1 g ceftriaxone; group B: ceftriaxone 1 g intravenous single dose followed by oral cefixime. When urine culture was received, both groups completed a 10 day treatment based in sensitivity studies. Only women with positive initial urine culture were included. After three days of treatment, clinical and bacteriological efficacy was assessed. Clinical response was classified as "cured" if acute symptoms (fever, urinary syndrome and flank pain) were settled. Bacteriological response was classified as: eradication, or no eradication. Results: Of 144 eligible patients, urine culture was positive in 54 of 72 (75%) women in group A and 51 of 72 (71%) in group B. There were no significant differences between groups in resolution of acute symptoms. Clinical cure was observed in 49 of 54 (91%) patients in the group A and in 47 of 51 (92%) patients in the group B (p = 0.68). After three days of treatment urine culture was negative for all patients. No adverse effects were observed in either of the groups. Conclusion: These data suggest that a intravenous single dose of ceftriaxone followed by oral cefixime is both effective and safe for the initial treatment of acute uncomplicated pyelonephritis in women. This regimen could be useful in managing selected patients with pyelonephritis as outpatients.